Peningkatan Peran Usaha Kesehatan Sekolah (UKS) Di Madrasah Aliyah Al-Falah Tolutu Kecamatan Tomini Kabupaten Bolaang Mongondow Selatan - Muhammad Fathurrachman Mantali; Adi Saputro; Vivi Sri Utami Gobel; Miranda Afriany Saputri Posangi; Geynaro Monthela Kangiras; Putri Amalia Dewantari Abjul; Sinta Ajuai (Jurnal Insan Pengabdian Indonesia, 2023)
The population for the age group of school children in Indonesia is very large, of course it is at risk of contributing to public health problems, especially at schools. One of the efforts that can be carried out at schools is to form a school health clinic (UKS). The role of the UKS in this regard is to empower students and the school community to get used to a clean and healthy lifestyle and first respond to health problems so as to reduce further risk factors. However in practice, UKS is often not a priority in the implementation of education in schools, many schools have not optimized UKS due to unsupportive infrastructure and a lack of understanding of health, one of which is at Madrasah Aliyah Tolutu. So a program to increase the role of the UKS at Madrasah Aliyah Al-Falah Tolutu was carried out as part of the Universitas Muhammadiyah Manado Community Service Program in 2023. This program was carried out in the form of counseling, outreach and direct training to students and the formation of UKS members. A series of activities were carried out on 127 students and 14 students were selected as UKS members. School students were very enthusiastic in participating in the socialization and training that had been held. The end result of this program is an increase in students' understanding of health and the formation of UKS cadres who are expected to continue their role to other students on an ongoing basis.